Risk Factors for Virus-induced Acute Respiratory Tract Infections in Children Younger Than 3 Years and Recurrent Wheezing at 36 Months Follow-Up After Discharge. Issue 2 (February 2017) - Nicolai, Ambra; Frassanito, Antonella; Nenna, Raffaella; Cangiano, Giulia; Petrarca, Laura; Papoff, Paola; Pierangeli, Alessandra; Scagnolari, Carolina; Moretti, Corrado; Midulla, Fabio
Abstract : Background: We sought to know more about how 14 common respiratory viruses manifest clinically, and to identify risk factors for specific virus-induced acute respiratory tract infections (ARTIs) in children younger than 3 years old and for wheezing at 36-month follow-up. Methods: We retrospectively studied the clinical records for 273 full-term children (median age, 2.9 months; range, 0.26–39; boys, 61.2%) hospitalized for ARTIs, whose nasopharyngeal specimen tested positive for a respiratory virus and 101 children with no history of respiratory diseases (median age, 8 months; range, 0.5–36.5; boys, 58.4%). At 12, 24 and 36 months after children's discharge, all parents were interviewed by telephone with a structured questionnaire on wheezing episodes. Results: The most frequently detected viruses were respiratory syncytial virus in bronchiolitis, human rhinovirus in pneumonia and human bocavirus in wheezing. Multivariate analysis identified, as risk factors for virus-induced ARTIs, the presence of siblings [odds ratio (OR): 3.0 (95% confidence interval [CI]: 1.8–5.2)], smoking cohabitants (OR: 2.3 (95% CI: 2–4.2)] and breastfeeding lasting less than 3 months [OR: 0.5 (95% CI: 0.3–0.9)]. The major risk factor for respiratory syncytial virus–induced ARTIs was exposure to tobacco smoke [OR: 1.8 (95% CI: 1.1–3.2)]. Risk factors for human rhinovirus–induced ARTIs were attending day-care [OR: 5.0 (95% CI: 2.3–10.6)] and high eosinophil blood counts [OR: 2.6 (95% CI: 1.2–5.7)]. The leading risk factor for recurrent wheezing was exposure to tobacco smoke [OR: 2.5 (95% CI: 1.1–15.6)]. Conclusions: Each respiratory virus leads to a specific clinical manifestation. Avoiding exposing children to tobacco smoke might restrict viral spread from sick parents and siblings to younger children, prevent severe respiratory diseases, and possibly limit sequelae.